HBOC in Europe - Hanne Meijers Heijboer (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 2016)
AbstractEurope has contributed to the majority of high-impact papers on genes and risk alleles in breast cancer and ovarian cancer susceptibility. Consortia like the Breast Cancer Linkage Consortium, Breast Cancer Association Consortium, and the Consortium of Investigators on Modifying genes in BRCA1/2, started from the nineties of the last century on. Many highly motivated participants throughout Europe, the US, Australia and elsewhere contributed to the formation of huge datasets. Instrumental of the success of the consortia was also the leadership and knowledge of Dough Easton, UK, on the statistics of cancer genetics. The consortia papers have produced the data on which national guidelines in HBOC were formulated in West-Europe, the US and worldwide. Genetic testing for HBOC is in most Western-European countries accepted and funded. Two decades after the identification of BRCA1 and BRCA2, attitudes towards genetic testing for HBOC are changing and becoming more ‘common’ practice. This offers opportunities to organize cancer genetic care more efficiently and at lower costs while informed decision making and consent of the patients remain in place.